(untitled) (Indonesian Journal of Civil Engineering Study, 2024)
Indonesia is an archipelagic country and is located on 3 plates which results in a country with many earthquakes. Apart from that, Indonesia also has good tourist areas and this country is visited by many foreign tourists. For this reason, there needs to be a place for these tourists to stay. Hotels are needed for areas with many tourist destinations. The planning of the hotel building must be done correctly because it is seen for commercial use. If good planning is not carried out, it can cause many fatalities due to structural failure. In this planning, the Etabs application is used to see the performance of structures that have been created manually, including the dimensions of columns, beams and plates. This planning refers to the use of the latest SNI to obtain maximum results. In this program, combinations are also added which include dead load, live load, wind load and earthquake load. The earthquake load can be seen from the existing spectrum response. In dimensioning the size of the structure, it can be explained that the dimensions of the 1st and 2nd floor columns are 50x50 cm, while for the 3rd to 6th floor columns they are 40x40 cm. The beam dimensions for a span of 5.4 m use a size of 45x30 cm, while for a span of 4.2 m use a size of 40x30 cm. The thickness of the plate used in this building is 12 cm thick with 2-way reinforcement type. The foundation uses a pile cap foundation with a size of 50 cm and a length per rod of 12 m. The pile cap has a concrete quality of K-350. In planning this structure, the type of material with iron quality BjTS 480 B and BjTP 240 is used, while the quality of concrete used is Fc’ 25 Mpa.